Clio e Psique: limites e perspectivas de diálogo - Franco Júnior, Hilário (2021)
Between history and psychoanalysis, one would expect a systematic and constant collaboration that does not occur due to specifics differences to the profile of each of those fields and a particular competition within the scientific universe. However, on the other hand, they have affinities concerning the purpose (understanding the human, both social and individual), the material used (fragments of the past observed), and the method adopted (inductive). Thus, a better reciprocal knowledge, proposed by this article, can allow a potentially favorable cooperation between the two disciplines.